My beginning as a nurse. A personal narrative - Cristo Manuel Marrero González (Universidad de Alicante, 2019)
In this document, I intend to narrate my main experiences in a brief and personal way when I started to work as a nurse in a hospital in Tenerife (Spain). These events happened in the second half of 2009. I reflect on the experience and I also try to argue my experiences based on the knowledge that I have acquired by developing a phenomenological doctoral thesis in which I study this event with nurses who begin to work in different health institutions in Tenerife